2021
DOI: 10.1007/s00784-021-04310-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of root canal therapy or full pulpotomy using two endodontic biomaterials in mature permanent teeth: a randomized controlled trial

Abstract: Objective The concept of minimally invasive endodontics recommends less-invasive vital pulp therapy (VPT) modalities over more aggressive traditional endodontic approaches in mature permanent teeth with carious pulp exposure, including irreversible pulpitis (IP) cases. Consequently, VPT needs to be compared with root canal therapy (RCT) in terms of treatment outcomes. This randomized clinical trial compares the results of full pulpotomy using two calcium-silicate cements, i.e., mineral trioxide ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…After reading the title and abstract of the literatures, 580 literatures were excluded. After reading the full text of the remaining 19 literatures, a total of 7 literatures met the inclusion and exclusion criteria of the study [10][11][12][13][14][15][16].…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the title and abstract of the literatures, 580 literatures were excluded. After reading the full text of the remaining 19 literatures, a total of 7 literatures met the inclusion and exclusion criteria of the study [10][11][12][13][14][15][16].…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…Five clinical trials [10][11][12][13]16] reported the postoperative clinical success rate, including 625 affected teeth, 305 in the experimental group and 320 in the control group. Heterogeneity test showed that there was no heterogeneity between studies (I 2 =0, P=0.99).…”
Section: Clinical Success Ratementioning
confidence: 99%
See 1 more Smart Citation
“…These hydrophilic CSCs have demonstrated more consistent clinical success (85-100%) when used as the pulpotomy medicament in mature permanent teeth. 40,41,42,43,44,45,46,47 The contrast in clinical outcomes was especially stark when direct comparisons were made between CH and CSCs for VPT. 39,48,49 New-generation bioactive CSCs are not only dimensionally stable with excellent sealing abilities, but also have beneficial biocompatible, immunomodulatory and osteogenic properties.…”
Section: Contemporary Pulpotomy Medicamentsmentioning
confidence: 99%
“…Pulpotomy has traditionally not been part of the treatment considerations for mature permanent teeth diagnosed with irreversible pulpitis. However, there is now increasing evidence from retrospective studies, 54,55,56 prospective cohort studies 40,41,47,57,58,59,60 and randomised controlled trials, 39,42,43,44,45,46,61,62,63,64,65,66,67,68,69,70 showing high success rates for pulpotomy in treating mature permanent teeth with irreversible pulpitis or carious pulp exposures (online Supplementary Table 1). Systematic reviews, meta-analyses and recent umbrella reviews (Table 2) have also concluded that pulpotomy could be a prospective substitute to conventional RCTx in managing vital mature permanent teeth diagnosed with irreversible pulpitis or carious pulp exposure.…”
Section: State Of Evidencementioning
confidence: 99%